Mutation patterns in recurrent and/or metastatic oropharyngeal squamous cell carcinomas in relation to human papillomavirus status. (1st February 2021) - Reder, Henrike; Wagner, Steffen; Wuerdemann, Nora; Langer, Christine; Sandmann, Sarah; Braeuninger, Andreas; Dugas, Martin; Gattenloehner, Stefan; Wittekindt, Claus; Klussmann, Jens Peter
Abstract: Patients with HPV‐driven (HPV+) oropharyngeal squamous cell carcinoma (OPSCC) have a significantly improved overall survival compared to patients with HPV‐negative (HPV−) OPSCC. Nevertheless, 13%–25% of patients with HPV+OPSCC develop local/distant recurrence (LDR) and have a course of disease similar to HPV−OPSCC. We hypothesize that HPV+OPSCCs of patients with LDR have a mutation frequency and pattern similar to HPV−OPSCCs, which is associated with severe outcome. We performed targeted next‐generation sequencing using a customized gene panel and compared data from 56 matched HPV+and HPV−OPSCC of patients with/without LDR regarding protein‐altering variants. Despite improved overall survival of patients with HPV+OPSCC, those who develop LDR show a strongly reduced survival rate that is similar or even worse compared to HPV−OPSCC patients. Overall, the number of mutations was similar in OPSCC of patients with and without LDR. In total and with respect to TP53, HPV−OPSCC had significantly more protein‐altering mutations than HPV+OPSCC. The number of mutations was similar in HPV−OPSCC of patients with and without LDR with the exception of FAT1, which was mutated more frequently in patients without LDR. In HPV+OPSCC, HRAS, PIK3R1, STK11 and TP63 were more frequently mutated in patients with LDR compared to patients without. HPV+OPSCC of patients with LDR have a similar mutation pattern as HPV−OPSCC, except TP53, which was mutated to a significantly lower extent. In conclusion, HPV−and HPV+OPSCC with LDR have similar mutation counts in the analyzed genes. We suspect that the number of mutations is not causal for disease progression, rather specific mutations could be important. Abstract : A subgroup of 13–25% of HPV‐driven (HPV+) OPSCC patients develop local or distant recurrence (LDR) and a severe course of disease similar to that of patients with HPV‐negative (HPV‐) OPSCC. Regarding the genes analyzed, we found that the HPV+OPSCC of patients with LDR carried a higher number of mutations than HPV+OPSCC of patients without LDR, with a similar mutation frequency as the HPV−OPSCC of LDR patients. Surprisingly, HPV−OPSCC of patients who did not develop LDR showed the highest number of mutations, suggesting that not the number but specific driver mutations are dominant factors for recurrence and that tumor‐specific neoantigens may play a role in a supportive antitumor immune response after therapy.